Ferroconcrete-like multilayer VACNTs@Si film for ultra-high areal and volumetric Li-ion storage - Li, Wangyang (2023)
Endowing Si-based anodes with both high areal and volumetric capacity is of great importance for their practical application, but this remains extremely challenging. Si-based anodes with high areal capacity are generally designed into porous structures to buffer the drastic volume change during charge/discharge process, which leads to a compromise in volumetric capacities. Herein, through a layer-by-layer technique, multilayer vertically aligned carbon nanotubes supported Si film (VACNTs@Si) with ferroconcrete-like sructures are developed to enhance both areal and volumetric capacities. The VACNTs frameworks facilitate electron transport and stabilize the andoe structure during cycling, while the Si cladding layer can provide a high capacity. A 3-layer VACNTs@Si film exhibits an superior areal/volumetric capacity of 3.59 mAh cm−2/3355.1 mAh cm−3, and high capacity retention of ∼79% after 200 cycles. The ferroconcrete-like structural design offers a promising strategy for the fabrication of the electrodes with ultra-high areal and volumetric capacities.